2022
DOI: 10.3390/tropicalmed7060082
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Hotspots of People Diagnosed of Tuberculosis with Addiction to Alcohol, Tobacco, and Other Drugs through a Geospatial Intelligence Application in Communities from Southern Brazil

Abstract: (1) Background: tuberculosis (TB) is considered one of the leading causes of death worldwide by a single infectious agent. This study aimed to identify hotspots of people diagnosed with tuberculosis and abusive use of alcohol, tobacco, and other drugs in communities through a geospatial intelligence application; (2) Methods: an ecological study with a spatio-temporal approach. We considered tuberculosis cases diagnosed and registered in the Notifiable Diseases Information System, which presented information on… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
1
1
0
Order By: Relevance
“…The result points to the presence of vulnerable populations in specific territories affecting people of specific socioeconomic status (social determinants of health). This points to specific locations having high TB prevalence and this is in support [ 17 ] that evidenced that TB burden was associated with specific communities, evidencing three high-risk detected in the Northwest, Northcentral and Metropolitan regions. In this sense, the high-risk were concentrated in the northern region (66.7%) similar to our study.…”
Section: Discussionsupporting
confidence: 74%
“…The result points to the presence of vulnerable populations in specific territories affecting people of specific socioeconomic status (social determinants of health). This points to specific locations having high TB prevalence and this is in support [ 17 ] that evidenced that TB burden was associated with specific communities, evidencing three high-risk detected in the Northwest, Northcentral and Metropolitan regions. In this sense, the high-risk were concentrated in the northern region (66.7%) similar to our study.…”
Section: Discussionsupporting
confidence: 74%
“…Among the two studies on tuberculosis in this Special Issue, Yu et al analyzed the diagnostic performance of QFG-GIT and the need for personalized cutoff values in diagnosis [ 10 ], while Scholze et al reported the hotspot regions with tuberculosis and alcohol, tobacco, and other drugs in southern Brazil using a geospatial intelligence application. The evidence suggested the existence of an association between tuberculosis and drug addiction within the investigated hotspot regions [ 11 ]. The use of geospatial videos to map environments with cholera risk in Congo was conducted by Curtis et al, highlighting the use of data science and machine learning to detect infectious diseases in health-risk regions [ 12 ].…”
mentioning
confidence: 99%